Financial Distress in Indonesian Mining Firms: Do Liquidity, Profitability, and Solvency Matter? - Sonia Rahmawati; Nurtati Nurtati; Risa Wahyuni EDT; Agusman Agusman (Al Dzahab, 2026)
Purpose: This study aims to examine whether liquidity, profitability, and solvency influence financial distress in Indonesian mining firms. The study focuses on mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period to determine whether these financial ratios play a significant role in explaining the occurrence of financial distress. Design/Methodology/Approach: This research employs a quantitative approach using secondary data obtained from the annual financial statements of mining companies listed on the IDX from 2021 to 2024. The sample was selected using purposive sampling, resulting in 13 companies that met the research criteria. The data were analyzed using multiple linear regression analysis to examine the relationship between liquidity, profitability, solvency, and financial distress. Hypothesis testing was conducted using the t-test to assess partial effects and the F-test to evaluate simultaneous effects. Findings: The results indicate that liquidity has a significant effect on financial distress in mining firms. Profitability also significantly affects financial distress, suggesting that the firm’s ability to generate profit plays an important role in preventing financial difficulties. In addition, solvency significantly influences financial distress, indicating that the firm’s level of leverage is associated with the likelihood of financial distress. Simultaneously, liquidity, profitability, and solvency significantly influence financial distress in Indonesian mining companies. Research Implications: The findings provide important implications for investors, creditors, and corporate managers in assessing the financial condition of firms, particularly in identifying early signals of financial distress through financial ratio analysis. This study also contributes to the financial management literature by providing empirical evidence on the role of liquidity, profitability, and solvency in explaining financial distress within the mining sector in an emerging market context.